Pre-School Education of the Children in the Family, the Organization and the Role of Education is Directed to the Person - Sh.A.Buranova; Y.A.Baratov (Genius Journals, 2022)
This article discusses the rolan and originality of student-centered education in the preschool and family, and the participation of family upbringing of the children in preschool
Keywords: Family Education; Family Participation; Individualization; Choice